2012
DOI: 10.1007/s10637-012-9866-y
|View full text |Cite
|
Sign up to set email alerts
|

A phase I study of IMP321 and gemcitabine as the front-line therapy in patients with advanced pancreatic adenocarcinoma

Abstract: Purpose This phase I study was conducted to determine the safety profile and maximum tolerated dose (MTD) of IMP321, a soluble lymphocyte activation gene-3 (LAG-3) Ig fusion protein and MHC Class II agonist, combined with gemcitabine in patients with advanced pancreatic adenocarcinoma. Patients and methods Patients with advanced pancreatic adenocarcinoma were treated with gemcitabine (1,000 mg/m2)(level 1), gemcitabine (1,000 mg/m2) plus IMP 321 at 0.5 mg (level 2) and 2.0 mg (level 3), respectively. Safety,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 29 publications
0
58
0
Order By: Relevance
“…Inspired by the success of checkpoint inhibitors, several other checkpoints are now under investigation as targets for monotherapy or as combination therapy, including lymphocyte activation gene-3 (LAG-3), T-cell immunoglobulin mucin-3 (TIM-3) and indoleamine-2,3-dioxygenase (IDO) (Brignone et al 2010, Wang-Gillam et al 2013, Beatty et al 2017). (Grosso et al 2007, Assal et al 2015.…”
Section: New Immune Checkpoint Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by the success of checkpoint inhibitors, several other checkpoints are now under investigation as targets for monotherapy or as combination therapy, including lymphocyte activation gene-3 (LAG-3), T-cell immunoglobulin mucin-3 (TIM-3) and indoleamine-2,3-dioxygenase (IDO) (Brignone et al 2010, Wang-Gillam et al 2013, Beatty et al 2017). (Grosso et al 2007, Assal et al 2015.…”
Section: New Immune Checkpoint Inhibitorsmentioning
confidence: 99%
“…In the last few years, studies have investigated the use of IMP321, a LAG-3-Ig recombinant fusion protein that antagonizes the normal function of LAG-3. These studies were focused on renal cell carcinoma (Brignone et al 2009), metastatic breast carcinoma (Brignone et al 2010) and advanced pancreatic adenocarcinoma (Wang-Gillam et al 2013). All these studies showed promising results regarding the effect of LAG-3 in reducing tumor size.…”
Section: New Immune Checkpoint Inhibitorsmentioning
confidence: 99%
“…When combined with paclitaxel, iMP321 has exerted immune enhancement and tumor inhibition with no significant iMP321-related adverse events [63]. in addition, in a phase i study focusing on pancreatic adenocarcinoma [19], iMP321 was tested combined with gemcitabine, appearing to be a safe regimen but only with limited antitumor responses possibly due to low doses of iMP321. So doses larger than 6 mg has been recommended in future US trials [19].…”
Section: Clinical Trials Focusing On Lag-3mentioning
confidence: 99%
“…in addition, in a phase i study focusing on pancreatic adenocarcinoma [19], iMP321 was tested combined with gemcitabine, appearing to be a safe regimen but only with limited antitumor responses possibly due to low doses of iMP321. So doses larger than 6 mg has been recommended in future US trials [19]. Besides, a small trial combining iMP321 and melanoma-associated antigen immunization in melanoma patients is still ongoing (nCT01308294).…”
Section: Clinical Trials Focusing On Lag-3mentioning
confidence: 99%
See 1 more Smart Citation